The development of interactive multimedia learning media on cell materials in Class XI IPA SMA Negeri 2 Kabanjahe - Nadia Br Ginting; Hudson Sidabutar (Educenter : Jurnal Ilmiah Pendidikan, 2022)
This study aims to develop and produce interactive multimedia-based biology learning media using a valid, practical and effective powerpoint media that can be applied as a biology learning medium on cell material. The type of research used is development research with a 4-D development model. This model includes four stages, namely defining, designing, developing and disseminating.  The results showed: (1) The validity of the media based on the assessment of media experts and material experts by getting an average percentage of 85.5% with the criteria of "very valid / very good". (2) The practicality of learning media based on student and teacher responses after using the media got an average percentage of 95.3% which included the "very practical" criteria. (3) The effectiveness of the media based on the results of student learning mastery after using interactive multimedia learning media is 86.1%. Then the calculation of the significance level is carried out with the ngain test score. From the results of manual calculations obtained n-gain score of 0.52. Based on the results of the study, the use of interactive multimedia learning media is said to be feasible with valid, practical and effective categories.